What Jonah knew : a novel - Graham, Barbara, 1947 November 11- (Harper, 2022)
Helen Bird will stop at nothing to find Henry, her musician son who has mysteriously disappeared in upstate New York. Though the cops believe Henry's absence is voluntary, Helen knows better. While she searches for him--joined finally by police--Jonah is born to Lucie and Matt Pressman of Manhattan. Lucie does all she can to be the kind of loving, attentive mother she never had, but can't stop Jonah's night terrors or his obsession with the imaginary "other mom and dog" he insists are real. Whether Jonah's anxiety is caused by nature or nurture--or something else entirely--is the propulsive mystery at the heart of the novel. All hell breaks loose when the Pressmans rent a summer cottage in Aurora Falls, where Helen lives. How does Jonah, at seven, know so much about Henry, Helen's still-missing son? Is it just a bizarre coincidence? An expression of Jung's collective unconscious? Or could Jonah be the reincarnation of Henry? Faced with more questions than answers, Helen and Lucie set out to make sense of the insensible, a heart-stopping quest that forces them to redefine not just what it is to be a mother or a human being, but the very nature of life--and death--because of what Jonah knows.